Android Based Health Service Information System for Registration of Patients at Gerung Hospital, Gerung Sub-District, West Lombok District - Mursid Raharjo; Rian Wahyul Ikhtiar; Ratih Wardani (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Background Health is one of the human rights whose fulfillment becomes government responsibility in accordance with the mandate of the law. Problems encountered hospitals today there are still many hospitals that handle too many patients, so they don't according to capacity, as a result patients are not served because the number of available health personnel is not comparable. Objective To determine the application of the Android-based information system design to improve outpatient services at Gerung Hospital. Methods The research instrument used in this study was the waterfall method, interview guidelines, observations, and test sheets for the system used in data collection within one month. Results The android-based outpatient registration study at the Gerung hospital was proven to improve patient care. This is evidenced by the increasing number of patients who can be treated per day. Conclusion The results of the proposed information system trial can overcome problems related to the quality of information from a system, namely: easy access to information, accuracy of information, timeliness, completeness of information and suitability of information.